Mastering audio the art and the science - Katz, Robert A. (Focal Press, Taylor & Francis Group, 2015)
"In an easy-to-grasp, holistic manner Mastering Audio: The Art and the Science, Third Edition unravels the technical mysteries that regularly challenge audio engineers. Including practical tips and real world experiences, Bob Katz explains the technical detail of the subject in his informative and humorous style. Completely reorganized to focus on workflow, this third edition details mastering by providing a step-by-step approach to the process. First covering practical techniques and basic theory, this industry classic also addresses advanced theory and practice. The book's new approach is especially suitable to accompany a one- or two-term course in audio and mastering. Completely rewritten and organized to address changes that will continue to influence the audio world, this third edition includes several new chapters addressing the influence of loudness measurement and assessment and provides explanation of how mastering engineers must integrate loudness measurement and PLR assessment in their mastering techniques. Mastering Audio: The Art and the Science, Third Edition also includes the newest approaches to equalization, monitor response measurement and correction, the psychoacoustics of clipping, an extended discussion of restoration and noise reduction techniques, an extended set of listening examples, and an updated chapter on surround mastering including coverage of Pure Audio BluRay"--